ROLE OF CT CHEST AS FIRST CHOICE FOR EARLY DIAGNOSIS OF COVID-19 PNEUMONIA EVEN IN RT-PCR NEGATIVE CASE - Asghar, Shoaib; Mustafa, Junaid; Durrani, Arsalan Ahmad Khan; Rehman, Habib Ur Rehman; Asghar, Sohaib; Usama, Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
The workup of corona virus disease (COVID-19) involves analyzing samples for acute or past presence of SARS-CoV-2 (virus). A detection of 2019 novel Corona virus (2019-nCov) by real-time reverse transcriptase polymerase chain reaction (RT-PCR) indicates current infection and positive IgG antibody level implies a prior infection. Imaging techniques like high resolution computed tomography (HRCT) chest and Xray chest helps in diagnosing and monitoring the disease. Most cases of 2019-nCov are mild and range from asymptomatic carriers to critical illness leading to acute respiratory distress, septic shock and multiorgan failure. We report two cases of COVID-19 who manifested with high grade fever, myalgias, cough and shortness of breath on minimal exertion. All baseline laboratory findings were normal. Initial RT-PCR was negative for oropharyngeal and nasopharyngeal swabs. CT Chest showing typical peripheral patchy and ground glass opacities bilaterally, other markers of infectivity followed by antibody titer confirms the disease.